2013
DOI: 10.1371/journal.pone.0078411
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Contributing to the Low Survival of Cervical Cancer Patients Undergoing Radiotherapy in Kenya

Abstract: BackgroundIn contrast to the developed nations, invasive cervical cancer (ICC) is the most common womens malignancy in Kenya and many other locations in sub-Saharan Africa. However, studies on survival from this disease in this area of the world are severely restricted by lack of patient follow-up. We now report a prospective cohort study of ICC in Kenyan women analysing factors affecting tumour response and overall survival in patients undergoing radiotherapy.Methods and FindingsBetween 2008 and 2010, 355 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
77
4
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 47 publications
9
77
4
2
Order By: Relevance
“…4). Our predicted survival probability was similar to a Kenyan study which showed a progressively lower survival probability with advancing stage of disease at diagnosis with an overall predicted 2-year survival of less than 20 % [15]. The overall median survival in the Kenyan cohort was 15.0 months following diagnosis and concurrent chemo-radiation therapy at a cervical cancer treatment center.…”
Section: Discussionsupporting
confidence: 82%
“…4). Our predicted survival probability was similar to a Kenyan study which showed a progressively lower survival probability with advancing stage of disease at diagnosis with an overall predicted 2-year survival of less than 20 % [15]. The overall median survival in the Kenyan cohort was 15.0 months following diagnosis and concurrent chemo-radiation therapy at a cervical cancer treatment center.…”
Section: Discussionsupporting
confidence: 82%
“…This has been reported in other studies. 7,24 Removing the tumor by surgery, using radiotherapy for primary treatment, and using chemotherapy to prevent metastasis may be more beneficial to the patient.…”
Section: Resultsmentioning
confidence: 99%
“…All but the least progressed stages of cervical cancer have high case-fatality rates in this region of the world (estimated to be greater than 50 %) due to poor access to effective treatment modalities. Women with advanced cases have 2-year survival rates of less than 20 % [3], and the average life-years lost due to cervical cancer is greater than 18 [4]. Effective screening programs utilizing cervical cytology have decreased the number of cases of ICC in developed nations.…”
Section: Introductionmentioning
confidence: 99%